Evidence for acquisition of virulence effectors in pathogenic chytrids - Sun, Guiling; Yang, Zefeng; Kosch, Tiffany A.; Summers, Kyle; Huang, Jinling (My University, 2011)
Background The decline in amphibian populations across the world is frequently linked to the infection of the chytrid fungus Batrachochytrium dendrobatidis (Bd). This is particularly perplexing because Bd was only recently discovered in 1999 and no chytrid fungus had previously been identified as a vertebrate pathogen. Results In this study, we show that two large families of known virulence effector genes, crinkler (CRN) proteins and serine peptidases, were acquired by Bd from oomycete pathogens and bacteria, respectively. These two families have been duplicated after their acquisition by Bd. Additional selection analyses indicate that both families evolved under strong positive selection, suggesting that they are involved in the adaptation of Bd to its hosts. Conclusions We propose that the acquisition of virulence effectors, in combination with habitat disruption and climate change, may have driven the Bd epidemics and the decline in amphibian populations. This finding provides a starting point for biochemical investigations of chytridiomycosis.